Insights into the biocompatibility of biodegradable metallic molybdenum for cardiovascular applications-a critical review - Mayers, Janina; Hofman, Brianna; Sobiech, Indie; Kwesiga, Maria P. (Frontiers in Bioengineering and Biotechnology, 2024)
Atherosclerotic cardiovascular disease (ACD) is the leading cause of death worldwide. The gold standard of treatment is the implantation of a permanent stent implant that is often associated with complications such as thrombus formation, vascular neointimal response and stent fracture, which altogether decrease the long-term safety and efficacy of the stent. Biodegradable metallic materials have become an attractive alternative because of the ability to facilitate a more physiological healing response while the metal degrades. Recently, Molybdenum (Mo) has been considered as a potential candidate due to its excellent mechanical and medical imaging properties. Moreover, the biomedical research studies performed to date have shown minimal adverse effects in vitro and in vivo. However, there are still concerns of toxicity at high doses, and the impact of the biochemical mechanisms of Mo on material performance especially in pathophysiological environments are yet to be explored. Mo is an essential co factor for enzymes such as xanthine oxidoreductase (XOR) that plays a critical role in vascular homeostasis and ACD progression. Herein, this review will focus on the biochemistry of Mo, its physiological and pathological effects with an emphasis on cardiovascular disease as well as the recent studies on Mo for cardiovascular applications and its advantages over other biodegradable metals. The limitations of Mo research studies will also be discussed and conclude with an outlook to move this revolutionary metallic biomaterial from the bench to the bedside.